The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1207/s15326942dn2903_5
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functions and Performance on High-Stakes Testing in Children From Urban Schools

Abstract: High-stakes achievement testing is a centerpiece of education reform. Children from socially disadvantaged backgrounds typically perform more poorly than their more advantaged peers. The authors evaluated 91 fifth-grade children from low-income urban schools using clinical neuropsychological tests and behavioral questionnaires and obtained fourth-grade scores on state mandated standards-based testing. Goals were to determine whether executive functions are selectively diminished in children from poor urban env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
43
1
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 16 publications
8
43
1
10
Order By: Relevance
“…For example, in a recent theoretical review of factors underpinning children's developing social skills, Beauchamp and Anderson (2010) argued that, with regard to influences of EF, attentional control (i.e., self-monitoring, response inhibition, and self-regulation) is especially critical. In contrast, other aspects of EF, such as working memory, appear to be critical for performance in academic tests of arithmetic or reading (e.g., Adams & Hitch, 1997;Cain, Oakhill, & Bryant, 2004;Waber, Gerber, Turcios, Wagner, & Forbes, 2006).…”
Section: Does Variation In Ef Growth Predict Teacher-rated Problem Bementioning
confidence: 98%
“…For example, in a recent theoretical review of factors underpinning children's developing social skills, Beauchamp and Anderson (2010) argued that, with regard to influences of EF, attentional control (i.e., self-monitoring, response inhibition, and self-regulation) is especially critical. In contrast, other aspects of EF, such as working memory, appear to be critical for performance in academic tests of arithmetic or reading (e.g., Adams & Hitch, 1997;Cain, Oakhill, & Bryant, 2004;Waber, Gerber, Turcios, Wagner, & Forbes, 2006).…”
Section: Does Variation In Ef Growth Predict Teacher-rated Problem Bementioning
confidence: 98%
“…Although the past decade has seen substantial growth in research on executive function in children and adolescents (Anderson, Jacobs, & Anderson, 2008;Bernstein & Waber, 2007), only more recently has there been research on relationships between executive function and real-world functioning such as academic performance in children (Clark, Pritchard, & Woodward, 2010) and adolescents (Waber, Gerber, Turcios, Wagner, & Forbes, 2006) or occupational functioning in adults (Barkley & Murphy, 2011). Even more recently, research has turned to developing interventions for executive dysfunction and measuring outcomes in the real world.…”
mentioning
confidence: 99%
“…Other studies have found that some children with EF may not show deficits that are significant (Nigg et al 2002;Sonuga-Barke 2002). The complexity of EF may be the reason why studies have been equivocal as to whether EF as a general domain is a major difficulty in ADHD (Anderson et al 2002;Denckla 2007;Nigg 2005;Vriezen and Pigott 2002;Waber et al 2006).…”
mentioning
confidence: 99%